An efficient time-domain fatigue analysis and its comparison to spectral fatigue assessment for construction steel 10HNAP. (December 2022) - Ronchei, Camilla; Vantadori, Sabrina; Marciniak, Zbigniew; Zanichelli, Andrea; Scorza, Daniela
Highlights: The accuracy of two fatigue criteria for multiaxial random loading is discussed. Fatigue tests related to 10NHAP steel and available in the literature are simulated. Fatigue lifetime and crack initiation path are estimated through the present criteria. The agreement between experimental data and theoretical results is satisfactory. The results are compared with those determined through three literature criteria. Abstract: In the present paper, the capability of two multiaxial fatigue criteria in both estimating the fatigue life and predicting the crack initiation path of metallic components under random loading is investigated. As a matter of fact, it is very difficult to find in the literature the predicted crack initiation path data when the loading has a random nature. To such an aim, an experimental campaign performed at the Opole University of Technology on a construction steel 10HNAP, under biaxial non-proportional random loading, is simulated by means of both a time-domain criterion and a frequency-domain one.